(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
Salman Rushdie’s memoirs, essays and novels contribute to the appreciation of the contradictions in his outlook on life. His experiences in his family enable Rushdie to make efforts for objective and tolerant judgement of British lifestyle and culture. However, his isolation from the society in Britain despite his struggle for adaptation to British cultural values cause contradictions in his cultural identity. While Rushdie expresses his allegiance to India and its culture in The Ground Beneath Her Feet (1999), he reflects his alienation from his homeland in this novel as well. Similarly, in his Imaginary Homelands (1981-1991) whereas Rushdie questions the injustice and inequality caused by imperialism in The New Empire within Britain (1982), he justifies the colonialist discourse in Kipling (1990). He elaborates on the contradictions in his outlook on life in terms of his cultural ambivalence in his fictions such as Midnight’s Children (1981) and Shame (1983). However, in his latest novel, Two Years, Eight Months and Twenty-Eight Nights (2015), Rushdie reflects his cultural identity conflict in terms of rationalism-mysticism dichotomy. With the use of allegory as well as the lack of linearity in time and space, Rushdie justifies his cultural ambivalence in relation to the dynamism of contemporary world. Thus, Rushdie’s latest novel invites reading for its representation of the oppositions in his approach to life.